2021
DOI: 10.2147/hiv.s328362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Reoccurrence of Opportunistic Infections Among Adult HIV/AIDS Patients Attending the ART Clinic at Public Health Facilities in Arba Minch Town, Southern Ethiopia

Abstract: Background: Opportunistic infections (OIs) in human immunodeficiency virus (HIV)positive individuals are infections that are more frequent or more severe than normal because of HIV-mediated immunosuppression. When these OIs occur in acquired immune deficiency syndrome (AIDS) patients in the form of relapse or reinfection, they are said to be a reoccurrence of OI. This study will try to identify gaps in addressing the burden in the study area. Methods: This cross-sectional study was conducted among 450 HIV/AIDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…All these findings could be explained by the difference between a relatively rural area (current study) and more urbanized settlements. This coincided with previous studies from Ethiopia and the USA, where it was demonstrated that rural/countryside patients with lower levels of education, low income, and limited access to healthcare facilities more readily develop OIs than others [25,[47][48][49].…”
Section: Discussionsupporting
confidence: 90%
“…All these findings could be explained by the difference between a relatively rural area (current study) and more urbanized settlements. This coincided with previous studies from Ethiopia and the USA, where it was demonstrated that rural/countryside patients with lower levels of education, low income, and limited access to healthcare facilities more readily develop OIs than others [25,[47][48][49].…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies from the USA [ 24 , 25 ] confirmed this. Furthermore, rural residents were not only the risky group for the occurrence but also for the recurrence of OIs [ 15 ] due to low income, lower level of education, and limited access to health care. Additionally, patients who had low cd4 counts had a higher hazard of OIs incidence than their counterparts because a weakened cellular immunity increases the risk of OIs incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as confirmed by a previous study, chronic disease increases the likelihood of OIs recurrence. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation